Pengaruh Rebusan Daun Salam terhadap Penurunan Tekanan Darah pada Lansia Penderita Hipertensi di RW 006 Sukmajaya Kabupaten Bogor Tahun 2025 - Anggito Hamdani; Solehudin Solehudin; Inas Syabanasyah (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2025)
Most of the hypertension sufferers in RW 006 Sukmajaya Village, Bogor Regency are >60 years old (elderly). One treatment option for hypertension sufferers is non-pharmacological therapy or herbal treatment. The research aims to determine the effect of giving bay leaf boiled water on reducing blood pressure in elderly people with hypertension. This type of research is quantitative with a Quasi-Experimental research design with a Two Group Pretest and Posttest Design. The sample in this study was 20 elderly people suffering from hypertension in RW 002 Sukmajaya Village, Bogor Regency, including 10 respondents as the Intervention group and 10 respondents as the Control group. Determining the number of samples using Purposive Sampling. This research data was processed using the Independent Sample T-test statistical test. Based on the statistical test results, the systolic blood pressure in the intervention group showed a p-value of 0.000 < 0.05 from the paired samples test, and the diastolic blood pressure showed a p-value of 0.005 < 0.05. Meanwhile, in the control group, the systolic blood pressure showed a p-value of 0.087 > 0.05 from the paired samples test, and the diastolic blood pressure showed a p-value of 0.093 > 0.05. It can be concluded that in the intervention group, the administration of boiled bay leaf water had an effect on reducing blood pressure in elderly individuals with hypertension. Meanwhile, in the control group, there was no change in blood pressure among elderly individuals with hypertension in RW 006, Sukmajaya Village, Bogor Regency, in 2025.